Design of a low-power compact CMOS variable gain amplifier for modern RF receivers - M. J. Alam; Mohammad Arif Sobhan Bhuiyan; Md Torikul Islam Badal; Mamun Bin Ibne Reaz; Noorfazila Kamal (Institute of Advanced Engineering and Science, 2020)
The demand for portability has speeded up the design of low-power electronic communication devices. Variable gain amplifier (VGA) is one of the most vulnerable elements of every modern receiver for the proper baseband processing of the signal. CMOS VGAs are generally suffered from low bandwidth and small gain range. In this research, a two-stage class AB VGA, each stage comprising of a direct transconductance amplifier and a linear transimpedance amplifier, is designed in Silterra 0.13-μm CMOS utilizing Mentor Graphics environment. The post-layout simulation results reveal that the VGA design achieves the widest bandwidth of more than 200 MHz and high gain range from -33 to 32 dB. The VGA dissipates only 2mW from a single 1.2 V DC supply. The core chip area of the VGA is also only 0.026 mm2 which is also the lowest compared to recent researches. Such a VGA will be a very useful module for all modern communication devices.